PENGARUH PENGELOLAAN KEUANGAN TERHADAP KINERJA KEUANGAN UKM (Studi pada UKM Batik di Kabupaten Bangkalan) - Suhartinah, Suhartinah (IQTISHODUNA, 2015)
This research was conducted to test the influence of financial management on financial performanceof UKM/ SMEs Batik in Bangkalan Regency. This research used census method therefore the sample in thisresearch is all UKM Batik in Tanjung Bumi Village, Bangkalan Regency. The total of them were 66 UKM Batik.The data collection methods in this research were Observation and Documentation Technique. The dataanalysis technique used in this research was Multiple Linear Regression. The result of this research was theVariable of Financing Activity was the strongest variable as the measurement of financial performance ofUKM in Bangkalan Regency. Meanwhile, the variable of Investment Activity was the weakest variable. Afterthat, both partially and simultaneously, the variable of operation activity, financing activity, and investmentactivity have role in the financial performance of UKM Batik in Bangkalan Regency